2014
DOI: 10.1515/astro-2017-0170
|View full text |Cite
|
Sign up to set email alerts
|

IO Com: Is it a Non-secondary Minimum Star?

Abstract: Abstract. Four-color photometry of IO Com, a detached eclipsing binary with a long period (∼ 53 d), was accomplished in [2004][2005][2006][2007][2008]. The absolute astrophysical and orbital parameters of the system were determined by the analysis of the light and radial velocity curves. No secondary minima in the light curves were detected. It was revealed that IO Com is the system with a highly eccentric orbit consisting of the components of mid-F spectral types. The calculated masses and radii of the primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The authors found the highest eccentricity for system ASAS 144242−5904.1 with e = 0.64, which was the maximum eccentricity found for eclipsing binary at that time. The rather questionable eclipsing system IO Com with its eccentric orbit e = 0.69 and P = 53 d is still quite problematic because no secondary eclipse has been detected (Taş & Evren 2014). The rich and precise data provided by the Kepler satellite (Borucki et al 2010) were analysed later and yielded a large number of detached and highly eccentric systems, one of which has an eccentricity of 0.845, but an orbital period of 265 d (Kjurkchieva et al 2017).…”
Section: Current Status Of the Topicmentioning
confidence: 99%
“…The authors found the highest eccentricity for system ASAS 144242−5904.1 with e = 0.64, which was the maximum eccentricity found for eclipsing binary at that time. The rather questionable eclipsing system IO Com with its eccentric orbit e = 0.69 and P = 53 d is still quite problematic because no secondary eclipse has been detected (Taş & Evren 2014). The rich and precise data provided by the Kepler satellite (Borucki et al 2010) were analysed later and yielded a large number of detached and highly eccentric systems, one of which has an eccentricity of 0.845, but an orbital period of 265 d (Kjurkchieva et al 2017).…”
Section: Current Status Of the Topicmentioning
confidence: 99%
“…The authors found the highest eccentricity for system ASAS 144242-5904.1 with e=0.64, which was the maximum eccentricity found for eclipsing binary at that time. The rather questionable eclipsing system IO Com with its eccentric orbit e=0.69 and P=53 d is still quite problematic because no secondary eclipse has been detected (Taş & Evren 2014). The rich and precise data provided by the Kepler satellite (Borucki et al 2010) were analysed later and yielded a large number of detached and highly eccentric systems, one of which has an eccentricity of 0.845, but an orbital period of 265 d (Kjurkchieva et al 2017).…”
Section: Current Status Of the Topicmentioning
confidence: 99%